Islamic-Based Play Learning for Early Childhood Cognitive Development: A Conceptual Literature Review - Wenti Suhartini; Ayu Wandira; Siti Norlia; Sri Putri; Putri, Hadisa (IJGIE (International Journal of Graduate of Islamic Education), 2024)
Early childhood is a crucial period for the formation of cognitive functions and basic character traits that influence long-term learning processes. In the context of Islamic education, the approach of learning based on Islamic values through play activities has rarely been studied conceptually to support cognitive stimulation in early childhood. There is a lack of literature discussing the systematic integration of Islamic values and play strategies within the framework of early childhood cognitive development. This study employs a conceptual literature review method with a descriptive-qualitative approach toward 38 relevant and curated scientific sources. The results of the study indicate that Islamic play activities such as role-playing stories of the prophets, worship simulations, and riddles based on moral values are able to stimulate children's thinking in a reflective and analytical manner. In addition, Islamic-based play learning provides meaningful learning experiences because it integrates symbolic, affective, and spiritual elements in an integrated manner. The conceptual model developed in this study demonstrates a functional relationship between the form of Islamic games, the Islamic values they contain, and the cognitive functions they stimulate. This research contributes theoretically to the development of an Islamic educational approach for early childhood and offers a practical framework for curriculum designers and educators in developing strategies that are contextual, spiritual, and cognitive simultaneously.